Adjustment of a multidimensional Rasch model to the five facet mindfulness questionnaire (FFMQ) administered to Yoga practitioners - Burga León, Andrés Alberto (2019)
This research aims to gather evidence on the validity of the internal structure of and estimate the reliability of the measurements from the FFMQ (Baer et al., 2006) using the multidimensional random coefficient multinomial logit model. Such instrument consists of 39 Likert-type items answered by selecting an option from a five-point rating scale on five dimensions: Observing, Describing, Acting with Awareness, Non-Judging and Non-Reactivity to Inner Experience. The analysis was conducted using data collected from an accidental non-probabilistic sample of 288 yoga practitioners who reported not being under a psychotherapeutic or psychopharmacological treatment.